Front Cover: Heterometallic [Cu2Ln3] (Ln = DyIII, GdIII and HoIII) and [Cu4Ln2] (Ln = DyIII and HoIII) Compounds: Synthesis, Structure, and Magnetism (Eur. J. Inorg. Chem. 8/2017). Issue 8 (17th February 2017) - Biswas, Sourav; Bag, Prasenjit; Das, Sourav; Kundu, Subrata; van Leusen, Jan; Kögerler, Paul; Chandrasekhar, Vadapalli
Abstract : The cover picture shows a pentanuclear and a hexanuclear complex based on Cu/Ln metal ions and the frequency dependence of their out‐of‐phase signals at various temperatures in the absence of a static bias dc field. These complexes were prepared by the subtle variation of the reaction conditions. Remarkably, both the complexes exhibit structural topology unprecedented in the Cu/Ln family. The Dy analogues display slow relaxation of magnetization. Details are discussed in the article by P. Kögerler, V. Chandrasekhar et al. on page 1129 ff (DOI:10.1002/ejic.201601210 ). For more on the story behind the cover research, see the Cover Profile (DOI:10.1002/ejic.201700102 ).